The anti-cancerous mechanism of licochalcone A on human hepatoma cell HepG2 based on the miRNA omics - Jun Wang; Xiuxiu Zhang; Zhijing Ni; Elnur Elam; Kiran Thakur; Kexin Li; Chuyan Wang; Jianguo Zhang; Zhaojun Wei (Food Science and Human Wellness)
To explore the function of licochalcone A as an anticancer phytochemical on HepG2 cells and investigate its potential mechanisms, we analyzed the microRNAs (miRNAs) expression profile of HepG2 cells in response to licochalcone A (70 μmol/L) in vitro. 102 dysregulated miRNAs were detected, and SP1 was expected as the transcription factor that regulates the functions of most screened miRNAs. A sum of 431 targets, the overlap of predicted mRNAs from TargetScan, miRDB, and miRtarbase were detected as the targets for these dysregulated miRNAs. FoxO signaling pathway was the hub pathway for the targets. A protein-protein interaction network was structured on the STRING platform to discover the hub genes. Among them, PIK3R1, CDC42, ESR1, SMAD4, SUMO1, KRAS, AGO1, etc. were screened out. Afterwards, the miRNA-target networks were established to screen key dysregulated miRNAs. Two key miRNAs (hsa-miR-133b and hsa-miR-145-5p) were filtered. Finally, the miRNA-target-transcription factor networks were constructed for these key miRNAs. The networks for these key miRNAs included three and two transcription factors, respectively. These identified miRNAs, transcription factors, targets, and regulatory networks may offer hints to understand the molecular mechanism of licochalcone A as a natural anticarcinogen.